Method for improving high-temperature creep resistance of TiAl alloy containing B2 phase
Through directional solidification and two-step heat treatment, the problem of high-temperature creep performance of B2 phase deterioration in TiAl alloy is solved, and the high-temperature creep resistance of TiAl alloy is significantly improved, which is suitable for the application of aero engine turbine blades.
Patent Information
- Application Number
- CN202510367092.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-03
AI Technical Summary
The B2 phase introduced in TiAl alloy results in insufficient high-temperature creep performance and is difficult to apply on aircraft engine turbine blades.
Through directional solidification and two-step heat treatment, columnar crystals and sheet structures arranged in a directionally are prepared, and the size of the B2 phase is reduced from 3~4μm to 0.1~0.3μm, improving the high-temperature creep resistance of TiAl alloy.
Under 900°C/120MPa, the minimum creep rate of TiAl alloy decreased by one order of magnitude, significantly improving the high-temperature creep resistance.
Smart Images

Figure CN120082823A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of TiAl alloys, and specifically provides a method for improving the high-temperature creep resistance of TiAl alloys containing B2 phase. Background Art
[0002] With the rapid development of China's aerospace industry, the requirements for aeroengine materials are increasing day by day. Reducing the weight of the engine and further improving the thrust-to-weight ratio are crucial for achieving the important goal of becoming a powerful aviation country. Currently, the blade material for the hot end components of engines is nickel-based superalloy, which has a relatively high density (8 g / cm 3 ), and is limited in development in terms of weight reduction, energy conservation, and emission reduction. TiAl alloys have the advantages of low density (3.9 g / cm 3 ), high specific strength, good high-temperature creep resistance and fatigue performance, etc., and have broad application prospects in major engineering fields such as aerospace. TiAl alloys have also been partially applied to the low-pressure turbine blades of aeroengines, with remarkable effects in energy conservation, emission reduction, and noise reduction.
[0003] In order to further increase the service temperature of TiAl alloys, researchers have added a large amount of high-melting-point β-stabilizing elements including Nb, W, Cr, V, etc. to TiAl to obtain new multi-phase TiAl alloys. While improving the high-temperature performance, a large number of ordered B2 phases will be introduced into the lamellar matrix. The B2 phase is a hard and brittle phase at room temperature and a soft and ductile phase at high temperature, which will cause room-temperature brittleness and deteriorate the high-temperature creep performance (B. Zhu et al. Mater Sci Eng A. 729 (2018) 86-93; Q. Wang et al. Intermetallic 94 (2018) 152-159). Therefore, most methods use hot working deformation and heat treatment at high temperatures to regulate the microstructure and B2 phase of TiAl alloys to obtain a uniform and fine equiaxed crystal structure to improve the mechanical properties of TiAl alloys (G. Zheng et al. Acta Mater. 225 (2022) 117585). However, aeroengine blades mainly bear the action of high temperature and centrifugal load, and the grain boundaries are usually relatively weak parts at high temperature. TiAl alloys with a fine equiaxed crystal structure often have insufficient creep resistance at high temperature due to more grain boundaries, and it is difficult to be applied to aeroengine turbine blades. Summary of the Invention
[0004] In order to solve the problem that the B2 phase in TiAl alloys deteriorates the high-temperature creep performance, the purpose of the present invention is to provide a method for improving the high-temperature creep resistance of TiAl alloys containing B2 phase.
[0005] In a first aspect, the present invention provides a method for improving the high-temperature creep resistance of a B2-phase-containing TiAl alloy, comprising the following steps:
[0006] (1) Directional solidification preparation: Cutting a master alloy ingot of a B2-phase-containing TiAl alloy to obtain a bar, and subjecting the bar to directional solidification;
[0007] (2) First heat treatment: Placing the directionally solidified TiAl alloy ingot into a heat treatment furnace, heating it to 1250 - 1350 °C under the protection of argon, holding for 20 - 60 minutes, and taking out the ingot to air-cool to room temperature;
[0008] (3) Second heat treatment: Placing the TiAl alloy ingot after the first treatment into a heat treatment furnace, heating it to 850 - 950 °C under the protection of argon, holding for 2 - 8 hours, and taking out the ingot to air-cool to room temperature.
[0009] Preferably, the B2-phase-containing TiAl alloy is a β-stabilizing element-containing TiAl alloy.
[0010] More preferably, the B2-phase-containing TiAl alloy, by atomic percentage, comprises: 45% - 48% of Al, 7 - 8% of Nb, 0.3 - 0.5% of W, 0.5 - 0.7% of Cr, 0.1% of B, and the balance of Ti.
[0011] Preferably, the master alloy ingot of the B2-phase-containing TiAl alloy is obtained by vacuum induction melting.
[0012] Preferably, during directional solidification, the pulling rate is 0.2 - 3.0 mm / min, the heating temperature is 1600 - 1700 °C, and the holding time is 10 - 30 min.
[0013] Preferably, the temperature of the first heat treatment is 1280 - 1300 °C, and the holding time is 25 - 35 min; the temperature of the second heat treatment is 940 - 960 °C, and the holding time is 3 - 4 h.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] (1) The present invention provides a method for improving the high-temperature creep resistance of a B2-phase-containing TiAl alloy. By means of directional solidification, columnar crystals and lamellar structures arranged in a direction and a B2 phase with a controllable content are obtained. Through two-step heat treatment, the size of the B2 phase is reduced from 3 - 4 μm to 0.1 - 0.3 μm.
[0016] (2) The present invention improves the high-temperature creep resistance of the B2-phase-containing TiAl alloy by the method of directional solidification + heat treatment. Under the conditions of 900 °C / 120 MPa, the minimum creep rate is reduced by one order of magnitude.
[0017] (3) The present invention optimizes the properties of TiAl alloys by combining the methods of directional solidification and heat treatment. The preparation process flow is simple and easy to implement, with strong controllability and high production efficiency, which is of great significance for promoting the application of TiAl alloys in aeroengine blades. Description of the Drawings
[0018] Figure 1 It is the macroscopic columnar crystal structure of the TiAl alloy after directional solidification in the embodiment.
[0019] Figure 2 It is the microscopic structure (a) of the cross-section of the TiAl alloy after directional solidification in the embodiment and its enlarged view (b).
[0020] Figure 3 It is the microscopic structure (a) of the cross-section of the TiAl alloy after directional solidification and heat treatment in the embodiment and its enlarged view (b).
[0021] Figure 4 It is the creep curve of the TiAl alloy at 900 °C / 120 MPa after directional solidification in the embodiment. Detailed Embodiments
[0022] The following further describes the present application in combination with specific embodiments.
[0023] It should be noted that the terms such as "upper", "lower", "left", "right", "middle" cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. The change or adjustment of their relative relationship, without substantial change in the technical content, should also be regarded as the scope of implementation of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the related listed items.
[0025] For those not specified in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For the reagents or instruments not specified by the manufacturer, they are all conventional products that can be obtained through commercial purchase.
[0026] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement, or value. Those skilled in the art can easily determine the degree of flexibility of a specific variable.
[0027] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.
[0028] The method for improving the high temperature creep resistance of TiAl alloy containing B2 phase according to the present invention comprises the following steps:
[0029] 1. Ingredients: According to the atomic percentage composition: Al is 46%~48%, Nb is 7~8%, W is 0.3~0.5%, Cr is 0.5~0.7%, B is 0.1% and Ti is the balance, respectively weigh the corresponding pure metal and intermediate alloy raw material particles, and perform ultrasonic cleaning and drying.
[0030] 2. Vacuum induction melting: A water-cooled copper crucible vacuum induction shell furnace is used for melting. First, high-purity raw materials are placed in the copper crucible in order of melting point, with high melting point materials at the bottom and low melting point materials at the top; the furnace door is closed, and the vacuum is evacuated to below 10Pa, and argon is filled into the furnace. Then, the vacuum is continued to be evacuated to below 3Pa, and argon is passed; the heating power is turned on, and the heating power is increased step by step to 70~80kW, and the maximum power is maintained for 15 minutes and electromagnetic stirring is performed; the power is turned off and cooled to room temperature, and then the heating is continued to be heated to 70~80kW for secondary remelting; the alloy melt is then poured into a preheated stainless steel mold, cooled to room temperature, and finally a TiAl master alloy ingot is obtained.
[0031] 3. Preparation for directional solidification: The above-mentioned TiAl master alloy ingot is cut by an electric spark wire to obtain a round rod and a bottom support of φ20~30mm; the round rod, the bottom support, the heating coil and the water-cooled copper crucible are installed in the directional solidification furnace according to the position relationship, and the cooling circulating water is turned on to check whether there is any water leakage in the furnace; the furnace door is closed, the vacuum is evacuated to below 10Pa and argon is passed, and the gas is washed 3 times; under the protection of argon, the smelting power is turned on, and the heating power is slowly increased to 40~60 kW (1600~1700℃), and the temperature is kept for 10~30min; the pulling rate is set within 0.2~3.0mm / min, and the upper feeding and lower pulling systems are turned on at the same time to carry out directional solidification experiments; after pulling a certain length, the power supply and the pulling system are turned off at the same time, and the furnace is cooled to room temperature, and finally a certain length of directional solidification TiAl alloy ingot is obtained.
[0032] 4. Determine the temperature of two-step heat treatment: Use thermodynamic phase diagram calculation software to calculate the equilibrium phase diagram of TiAl alloy. Based on the TiAl alloy database, select elements and content ranges and possible phase types, select uniaxial equilibrium mode to calculate the equilibrium phase diagram in the range of room temperature to 1700℃, and obtain the corresponding phase transition temperature. Use differential scanning calorimeter to test TiAl alloy, take a small sample and put it into a crucible and weigh it, set the temperature range from room temperature to 1700℃, the heating rate is 10℃ / min, the atmosphere is argon, and the corresponding curve is obtained after testing to obtain the phase transition temperature range.
[0033] 5. The first step of heat treatment: place the directionally solidified TiAl alloy ingot into a heat treatment furnace, heat it to 1250~1350℃, keep it warm for 20~60 minutes, then take out the ingot and air cool it to room temperature.
[0034] 6. Second step: Place the TiAl alloy ingot after the first step treatment into a heat treatment furnace, heat it to 850-950°C, keep it warm for 2-8 hours, then take out the ingot and air cool it to room temperature to prepare a directionally solidified B2 phase-containing TiAl alloy with optimized creep properties.
[0035] Example:
[0036] 1. Ingredients: According to the atomic percentage composition: Al is 46%, Nb is 7%, W is 0.4%, Cr is 0.6%, B is 0.1% and Ti is the balance, respectively weigh the corresponding pure metal and intermediate alloy raw material particles, and perform ultrasonic cleaning and drying.
[0037] 2. Vacuum induction melting: A water-cooled copper crucible vacuum induction shell furnace is used for melting. First, high-purity raw materials are placed in the copper crucible in order of melting point, with high melting point materials at the bottom and low melting point materials at the top; the furnace door is closed, and the vacuum is evacuated to below 10Pa, and argon is filled into the furnace to 300Pa, and then the vacuum is continued to be evacuated to below 3Pa, and argon is passed to 300Pa; the heating power is turned on, and the heating power is increased step by step to 70~80kW, and the maximum power is maintained for 15 minutes and electromagnetic stirring is performed; the power is turned off and cooled to room temperature, and then the heating is continued to be heated to 70~80kW for secondary remelting; the alloy melt is then poured into a preheated stainless steel mold, cooled to room temperature, and finally a TiAl master alloy ingot is obtained.
[0038] III. Directional solidification preparation: The master alloy ingot prepared in the above steps is cut by wire electrical discharge machining to obtain round bars with a diameter of φ20 - 30 mm and a base; the round bars, base, heating coil, and water-cooled copper crucible are installed in a directional solidification furnace according to the positional relationship, and the cooling circulating water is turned on to check whether there is water leakage in the furnace; the furnace door is closed, the vacuum is pumped to below 10 Pa and argon is introduced to 300 Pa, and the gas is washed 3 times; under the protection of argon, the melting power supply is turned on, and the heating power is slowly increased to 55 kW and kept warm for 10 min; the drawing rate is set at 0.5 mm / min, and at the same time, the upper feeding and lower drawing systems are turned on to conduct a directional solidification experiment; after drawing a certain length, the power supply and the drawing system are turned off simultaneously and cooled to room temperature, and finally a directional solidification TiAl alloy ingot (Before HT) with a certain length is obtained. The macroscopic structure photograph is as shown in Figure 1 , and it can be seen from Figure 1 that after directional solidification, the macroscopic structure of the TiAl alloy is a directional columnar crystal structure distributed along the heat flow direction, and the average width of the columnar crystals is 286 μm. The backscattered electron image of the microstructure of the cross-section of the ingot is as shown in Figure 2 . It can be seen that the microstructure consists of a lamellar structure composed of α 2 and γ, as well as large blocky B2 phases distributed between or inside the lamellae. The average size of the B2 phases is approximately 3 - 4 μm.
[0039] IV. Determination of heat treatment temperature: The equilibrium phase diagram of the TiAl alloy is calculated using thermodynamic phase diagram calculation software. Based on the TiAl alloy database, the selected elements and content ranges and possible phase types are determined, and the uniaxial equilibrium mode is selected to calculate the equilibrium phase diagram in the range of room temperature to 1700 °C to obtain the corresponding phase transformation temperatures. The TiAl alloy is tested using a differential scanning calorimeter. A small sample is placed in a crucible and weighed, the temperature range is set from room temperature to 1700 °C, the heating rate is 10 °C / min, and the atmosphere is argon. After testing, the corresponding curve is obtained to get the phase transformation temperature range.
[0040] V. First heat treatment: According to the heat treatment temperature determined in step IV, the directionally solidified TiAl alloy ingot is placed in a heat treatment furnace, heated to 1290 °C under the protection of argon, kept warm for 20 minutes, and then the ingot is taken out and air-cooled to room temperature.
[0041] VI. Second treatment: According to the heat treatment temperature determined in step IV, the TiAl alloy ingot after the first treatment is placed in a heat treatment furnace, heated to 950 °C under the protection of argon, kept warm for 4 hours, and then the ingot is taken out and air-cooled to room temperature to prepare a TiAl alloy (After HT) with optimized creep properties. The backscattered electron image of the microstructure is as shown in Figure 3 . It can be seen that the microstructure consists of α 2It is composed of a lamellar structure formed by α and γ, and fine and dispersed B2 phases distributed between or within the lamellae. The average size of the B2 phase is approximately 0.1 - 0.3 μm, and the size of the B2 phase is significantly decomposed and refined compared to that before heat treatment. The creep curve of the sample under the conditions of 900 °C / 120 MPa is as shown in Figure 4 . The results show that the creep rupture life of the directionally solidified TiAl alloy before heat treatment is 89 hours, and the minimum creep rate is 2.6×10 -7 s -1 . The creep rupture life of the directionally solidified TiAl alloy after heat treatment is 114 hours, the creep rupture life is improved, the minimum creep rate is 2.4×10 -8 s -1 , and the minimum creep rate is reduced by one order of magnitude, and the high-temperature creep resistance is significantly improved.
Claims
1. A method for improving the high temperature creep resistance of a TiAl alloy containing a B2 phase, characterized in that: The steps include: (1) Directional solidification preparation: cutting a master alloy ingot containing a B2 phase TiAl alloy to obtain a rod, and performing directionally solidification on the rod; (2) First step of heat treatment: Place the directionally solidified TiAl alloy ingot into a heat treatment furnace, heat it to 1250~1350℃ under the protection of argon gas, keep it warm for 20~60 minutes, take out the ingot and air cool it to room temperature; (3) Second step heat treatment: Place the TiAl alloy ingot after the first step treatment into a heat treatment furnace, heat it to 850-950°C under the protection of argon gas, keep it warm for 2-8 hours, take out the ingot and air cool it to room temperature.
2. The method according to claim 1, characterized in that The TiAl alloy containing B2 phase is a TiAl alloy containing β-stabilizing elements.
3. The method according to claim 1 or 2, characterized in that The B2 phase-containing TiAl alloy includes, by atomic percentage, 45% to 48% Al, 7% to 8% Nb, 0.3% to 0.5% W, 0.5% to 0.7% Cr, 0.1% B and the balance Ti.
4. The method according to claim 1, characterized in that The master alloy ingot containing the B2 phase TiAl alloy is obtained by vacuum induction melting.
5. The method according to claim 1, characterized in that During directional solidification, the pulling rate is 0.2~3.0mm / min, the heating temperature is 1600~1700℃, and the holding time is 10~30min.
6. The method according to claim 1, characterized in that The first step of heat treatment temperature is 1280~1300℃, and the holding time is 25~35min.
7. The method according to claim 1, characterized in that The second step heat treatment temperature is 940~960℃, and the insulation time is 3~4h.
Citation Information
Cited By
Particle-reinforced equiaxial / columnar original beta grain titanium-based composite material and preparation method thereof
CN120989443A
Particle reinforced equiaxed / columner primary beta grain titanium matrix composite and method of making
CN120989443B